The implementation of the new developments under the new commercial companies’ law - Ahmed Ali Al-Khassawneh, Yasar Fawaz Alhnaiti, Ammar Jreisat, (Opción, 2019)
The aim of the study is to investigate the implementation of the new developments under the new commercial companies’ law on the UAE economy via comparative qualitative research methods. As a result, the New Commercial Companies Law (CCL) provides a one-year period for existing companies to amend their constitutional documents, and contains strengthened penalties for breach. In conclusion, the new law introduces changes which will affect some of the structures used by foreign investors to establish businesses in the UAE. This gives greater guarantee and effectiveness to the companies in their approaches and helps avoid the obstacles they may encounter.